Evaluasi Implementasi Strategi Blue Ocean dalam Pengembangan Layanan Unggulan Rumah Sakit - Purwadhi, Purwadhi; Widjaja, Yani Restiani; Windaswari, Gusti Ayu Rahayu; Haliem, Helena Claudia (Universitas Medan Area, 2025)
The Blue Ocean Strategy emerges as an alternative approach to create new value through the development of flagship services that have not yet been explored by competitors. This study aims to evaluate the implementation of the Blue Ocean Strategy in the development of flagship services at XYZ Hospital. The research employs a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews and internal hospital documentation, and analyzed using the ERRC Grid and Strategic Canvas frameworks. The results show that XYZ Hospital successfully created new digital and early detection–based services, which led to an increase in patient visits, satisfaction, service time efficiency, and the strengthening of the institution’s image. However, the implementation of the strategy faced challenges such as regulatory constraints, human resource resistance, and budget limitations. The success of this strategy was supported by strong management commitment and an adaptive organizational culture. This study concludes that the Blue Ocean Strategy can be effectively implemented in the context of Indonesian hospitals when aligned with market needs and organizational capacity